2019
DOI: 10.5194/wes-4-563-2019
|View full text |Cite
|
Sign up to set email alerts
|

Improving mesoscale wind speed forecasts using lidar-based observation nudging for airborne wind energy systems

Abstract: Abstract. Airborne wind energy systems (AWESs) aim to operate at altitudes above conventional wind turbines where reliable high-resolution wind data are scarce. Wind light detection and ranging (lidar) measurements and mesoscale models both have their advantages and disadvantages when assessing the wind resource at such heights. This study investigates whether assimilating measurements into the mesoscale Weather Research and Forecasting (WRF) model using observation nudging generates a more accurate, complete … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…A common proxy for atmospheric stability is the Obukhov length (Obukhov, 1971;Sempreviva and Gryning, 1996), a metric that exclusively uses surface data (see section 2.2 and equation 1). Previous studies (Sommerfeld et al, 2019b) showed that Obukhov-length-classified wind speed profiles diverge with height, especially during neutral and stable conditions. This indicates vertically heterogeneous atmospheric stability and suggests that surfacebased stability categorization is insufficient for higher altitudes.…”
Section: Clustering Of Wind Conditions 135mentioning
confidence: 92%
See 3 more Smart Citations
“…A common proxy for atmospheric stability is the Obukhov length (Obukhov, 1971;Sempreviva and Gryning, 1996), a metric that exclusively uses surface data (see section 2.2 and equation 1). Previous studies (Sommerfeld et al, 2019b) showed that Obukhov-length-classified wind speed profiles diverge with height, especially during neutral and stable conditions. This indicates vertically heterogeneous atmospheric stability and suggests that surfacebased stability categorization is insufficient for higher altitudes.…”
Section: Clustering Of Wind Conditions 135mentioning
confidence: 92%
“…"Onshore" wind data at the Pritzwalk Sommersberg airport (lat: 53 • 10 47.00 N, lon: 12 • 11 20.98 E) in northern Germany and comprises 12 months of WRF simulation between September 2015 and September 2016. The area surrounding the airport mostly consists of flat agricultural land with the town of Pritzwalk to the south and is therefore a fitting location for wind energy generation (See (Sommerfeld et al, 2019a) and (Sommerfeld et al, 2019b) for details). The FINO3 research platform in the North Sea (lat: 55 • 11, 7 N, lon: 7 • 9, 5 E) was chosen as a representative "offshore" location due to the proximity to several offshore wind farms and the amount of comprehensive reference measurements (Peña et al, 2015).…”
Section: Wind Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Results in this study are exclusively based on WRF mesoscale simulations, since measuring wind conditions at mid-altitudes is difficult due to reduced data availability [137] and measurements are hard to find, proprietary or confidential. We compare AWES performance for an onshore location in northern Germany near the city of Pritzwalk [136] and an offshore location at the FINO3 research platform in the North Sea. WT and AWES performance using logarithmic wind profiles are compared as reference.…”
Section: Introductionmentioning
confidence: 99%